Managing Athletic Department Touch Points: A Case Study of One Institution Using Importance-Performance Analysis - Chard, Chris; MacLean, Joanne; Faught, Brent (Journal of Intercollegiate Sport, 2013)
Athlete recruitment and delivery of the sport experience are critical components in determining the success of intercollegiate athletic teams and programs. Here, the athletic department brand and the associations of the brand achieved through “touch points” influence student-athletes’ perceptions of the athletic department. The purpose of this study therefore was to understand the perceptions held by student-athletes about the brand of the athletic department. Importance-Performance Analysis (IPA) and brand touch point theory were used to accomplish the study’s objective. Specifically, the authors analyzed surveys from 149 student-athletes based at one university in Ontario, Canada to consider athletic department “touch points.” The results proved beneficial for highlighting areas of discrepancy between deemed importance and performance on key recruitment and delivery attributes including scholarship support, spectator support, special treatment, recognition, and quality of facilities.